Pemikiran Kritis Abu Zaid Terhadap Wacana Keagamaan: Implikasinya Dalam Pengembangan Pembelajaran Teologi di PTAI - suparjo suparjo (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2015)
: Abu Zaid finds that all religious thoughts have been tightly affected by social, cultural, economic, and political interests and tendencies until there are so many difficulties to differentiate between the essence of Islamic doctrines and their interpretations. Therefore, he tries to deliberate people from such contaminated Islamic doctrines. Alternatively, he calls them to read Islamic sources and thoughts critically, scientifically, and productively. Pedagogically, Abu Zaidâ€™ intellectual capacity had been built for a long time through conducive processes of education and impressive experiences in religious life. Actually, an intellectual capacity Abu Zaid had achieved is a part of ultimate goal of Islamic Higher education. Accordingly, to produce students as smart as Abu Zaid, a lecturer shall apply active learning, a learning that empowers all students along with their all potencies. To give a kind of focused description, this paper just draws an example way of handling an active learning process of class of Theology by which students can develop their thoughts as deliberately as Abu Zaid had done.Â Â